Perkembangan Teori Belajar dan Aplikasinya pada Pembelajaran Matematika - Widia, Widia; Rahmasyahfitri, Rahmasyahfitri; Fadillah, Siti; Damanik, Khoirul Fahmi; Lubis, Reza Handika Winata (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
Mathematics plays a strategic role in developing logical, analytical, and critical thinking skills that support various scientific fields. However, students often perceive mathematics as a difficult subject, necessitating an effective learning approach grounded in established learning theories. This study aims to analyze the evolution of learning theories—including behaviorism, cognitivism, constructivism, and social learning—and their applications in mathematics education, while also providing recommendations for effective learning strategies. Using a qualitative literature review approach, this research examines data from various academic sources. The findings indicate that each learning theory has strengths and limitations: behaviorist theory effectively trains basic skills, cognitive theory enhances conceptual understanding, constructivist theory enables students to build knowledge through direct experience, and social learning theory underscores the importance of interaction and collaboration. This study suggests integrating multiple learning theories to enhance students' comprehension, motivation, and engagement in mathematics. Additionally, it emphasizes the need for teacher training to ensure the effective application of these theories in the classroom.